Aptitude and Academic Performance Among Medical Students of Bangladesh (Bangladesh Journal of Medical Education, 2023)
Background: aptitude is one of the major determinants of effectiveness of students’ learning’.Aims and Objectives: To find out the relationship between aptitude and academic performance among medical students of Bangladesh.Materials and Methods: This cross-sectional study was conducted to assess the relationship between aptitude tests’ scores and academic performances of the medical students of Bangladesh. A total of 436 student respondents participated in this study from eight purposively selected of Bangladesh those are located at Dhaka. As well as outside Dhaka from January to December 2022 using a pretested semi-structured self-administered questionnaire.Results: This study Finding showed that very few medical students scored ≥60% in verbal reasoning (17.4%), abstract reasoning (21.8%), situational judgement tests (6.2%) and total aptitude tests (12.4%); but the numerical reasoning was good (60.1%).  no significant association was found between deferent aptitude tests’ scores and academic performances of the medical students.Conclusion:  It can be recommended that we can consider to introduce aptitude tests in our medical student selection process so that students with good aptitude tests scores can enrolled in the course.Bangladesh Journal of Medical Education Vol.14(2) July 2023: 3-7